Causes of Communal Boundary Conflicts in Nigeria: A Study of Mkpani-Nko Boundary Relations of Old Upper Cross River Region - Okoi , Ibiang Obono; Offor, Ajeh Ekpo (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
The research primarily considers the causes of communal boundary conflicts in Nigeria using Mkpani-Nko boundary relations of the old upper Cross River Region as a focal point. Evidence indicates that for several decades, both communities of Mkpani and Nko in the old Upper Cross River Region during the colonial retro had betrothed one another in a long-drawn-out borderline skirmish that originated from wilderness disagreements. The research also examined why farmland, a fixed and free gift of nature from God was and has remained a principal factor in most of the boundary conflicts that occurred in the region. The historical methodology adopted for the research involved the use of both primary and secondary sources with the primary source largely made up of oral interviews, while the secondary source had to do with both published and unpublished works on the subject matter. Findings suggest that apart from farmland being the principal cause of the conflict, there were other remote and immediate causes responsible for the conflict with its attendant negative effects such as loss of lives, destruction of property, insecurity, and stained relationship. The paper recommends that an arbitration committee that will always be prompt to settle land disputes between and among communities in the State should be established while Peace and Reconciliation Standing Committee as well should also be established to settle non-land disputes. The paper concludes that government should always be forthright, proactive, and prompt in dealing with the communal crisis of any kind in the state to always avoid escalation.